Themes of Good vs. Evil in Amish Tripathi’s Shiva Trilogy - Nysha Divakar (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
Myth is a traditional narrative rooted in the ancient past of a culture, often used to explain social, moral, or environmental phenomena. Situated between anthropology, philosophy, and literature, myth simultaneously denotes belief, symbolism, and imaginative truth. Tradition, closely linked to myth, refers to belief systems and behavioural patterns transmitted across generations. Amish Tripathi’s Shiva Trilogy reimagines Indian mythology by presenting the theme of good versus evil not as a rigid binary but as a complex and evolving moral framework. Through the humanisation of Shiva and the reinterpretation of mythic institutions such as Meluha, the Chandravanshis, and the Somras, the trilogy questions absolute moral positions. Evil is not portrayed as an external force but as the outcome of flawed choices, rigid ideologies, and unintended consequences. This paper examines how Tripathi deconstructs the conventional understanding of good and evil, presenting them as relative and contextual rather than absolute. By analysing characters, societies, and ethical dilemmas within the trilogy, the study highlights how mythology is used as a tool to explore moral ambiguity and contemporary social concerns. The paper argues that the Shiva Trilogy presents good and evil as dynamic concepts shaped by perception, responsibility, and balance.